Hubungan Beban dengan Kualitas Hidup Caregiver dalam Merawat Anak Berkebutuhan Khusus - Wulan Krisnandari, A. A. Istri; Sri Rahyanti, Ni Made; Sriasih, Ni Kadek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Caregivers (parents) often experience the burden of caring for children with special needs. This burden can affect the quality of life of parents. The aim of this research is to determine the relationship between burden and the quality of life of caregivers (parents) in caring for children with special needs. This research uses a correlative descriptive research design with a cross-sectional approach. This research uses a purposive sampling method, the number of samples in this study was 97 people, with inclusion criterias: parents of children with special needs who were registered as active students at SLB Negeri 1 and SLB Negeri 3 Denpasar, willing to take part in the research and sign the research consent form. Data collection was carried out using the Zarit Burden Interview (ZBI) and WHO Quality of Life–BREF questionnaires. Data were analyzed using descriptive tests and Spearman-Rho analysis. The research results showed that the majority of caregivers had a burden in the little/no burden category (51,5%) and a quality of life in the moderate quality of life category (54,6%). Regarding the relationship between burden and quality of life of caregivers in caring for children with special needs, with a significance value of 0,125 (p-value 0,05), this shows that there is no significant relationship between these two variables. The conclusion obtained in this research is that there is a relationship between burden and the quality of life of caregivers in caring for children with special needs at SLB Negeri 1 and SLB Negeri 3 Denpasar.